Neoadjuvant immunotherapy is reshaping cancer management across multiple tumour types: The future is now!. (July 2021) - Maio, Michele; Blank, Christian; Necchi, Andrea; Di Giacomo, Anna Maria; Ibrahim, Ramy; Lahn, Michael; Fox, Bernard A.; Bell, R. Bryan; Tortora, Giampaolo; Eggermont, Alexander M.M.
Abstract: The Italian Network for Tumor Biotherapy (Network Italiano per la Bioterapia dei Tumori [NIBIT]) Foundation hosted its annual 2020 Think Tank meeting virtually, at which representatives from academic, clinical, industry, philanthropic, and regulatory organisations discussed the role of neoadjuvant immunotherapy for the treatment of cancer. Although the number of neoadjuvant immunotherapeutic trials is increasing across all malignancies, the Think Tank focused its discussion on the status of neoadjuvant trials in cutaneous melanoma (CM), muscle-invasive urothelial bladder cancer (MIBC), head and neck squamous cell carcinoma (HNSCC), and pancreatic adenocarcinoma (PDAC). Neoadjuvant developments in CM are nothing short of trailblazing. Pathologic Complete Response (pCR), pathologic near Complete Response, and partial Pathologic Responses reduce 90–100% of recurrences. This is in sharp contrast to targeted therapies in neoadjuvant CM trials, where only a pCR seems to reduce recurrence. The pCR rate after neoadjuvant immunotherapy varies among the different malignancies of CM, MIBC, HNSCC, and PDAC and may be associated with different reductions of recurrence rates. In CM, emerging evidence suggests that neoadjuvant immunotherapy with anti-CTLA-4 plus anti-PD1 is a game changer in patients with palpable nodal Stage III or resectable Stage IV disease by curing more patients, reducing recurrences and the need for surgical interventions, such as lymph node dissections and metastasectomies. The Think Tank panel discussed future approaches on how to optimise results across different tumour types. Future approaches should include reducing monocyte-mediated (tumour-associated macrophages) and fibroblast-mediated (cancer-associated fibroblasts) barriers in the tumour microenvironment to facilitate the recruitment of immune cells to the tumour site, to reduce immune-suppressive mediators, and to increase antigen presentation at the site of the tumour. Highlights: Neoadjuvant immunotherapy will revolutionise patient management in various tumours. Neoadjuvant immunotherapy with anti-CTLA4 plus anti-PD1 is most effective in melanoma. In melanoma neoadjuvant immunotherapy is superior to neoadjuvant targeted therapy. High to encouraging activity is seen in bladder, head and neck, and pancreatic cancers. More cures and less surgery with neoadjuvant immunotherapy in Stage III/IV melanoma.